2005
DOI: 10.1088/0264-9381/22/7/013
|View full text |Cite
|
Sign up to set email alerts
|

Computations of primordial black-hole formation

Abstract: Abstract. Results are presented from general relativistic numerical computations of primordial black-hole formation during the radiation-dominated era of the universe. Growing-mode perturbations are specified within the linear regime and their subsequent evolution is followed as they become nonlinear. We use a spherically symmetric Lagrangian code and study both super-critical perturbations, which go on to produce black holes, and sub-critical perturbations, for which the overdensity eventually disperses into … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

10
367
3

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 319 publications
(380 citation statements)
references
References 45 publications
10
367
3
Order By: Relevance
“…In this situation, the coupled system of Einstein and hydrodynamical equations can be solved analytically, and one finds that the small perturbations in energy density, velocity, etc are generated uniquely by the curvature profile, which is then the only quantity that needs to be specified. In [12] the numerical scheme developed in [11] was modified so as to use initial data coming from this quasi-homogeneous solution, and the values of δ c found in [11] were confirmed. The crucial point of this argument is that the main perturbations of interest in this cosmological context are ones coming from inflation which then re-enter the cosmological horizon at later times.…”
Section: Introductionmentioning
confidence: 80%
See 4 more Smart Citations
“…In this situation, the coupled system of Einstein and hydrodynamical equations can be solved analytically, and one finds that the small perturbations in energy density, velocity, etc are generated uniquely by the curvature profile, which is then the only quantity that needs to be specified. In [12] the numerical scheme developed in [11] was modified so as to use initial data coming from this quasi-homogeneous solution, and the values of δ c found in [11] were confirmed. The crucial point of this argument is that the main perturbations of interest in this cosmological context are ones coming from inflation which then re-enter the cosmological horizon at later times.…”
Section: Introductionmentioning
confidence: 80%
“…In the 1980s, attention shifted mainly to the cosmological consequences that a population of PBHs would have, and this was extensively studied in various scenarios (see, for example, the recent review by Carr [7]). In 1999 Niemeyer & Jedamzik [8] returned to the issue of making numerical calculations of the PBH formation process, and they were subsequently followed in this by other groups [9,10] including ourselves [11,12,13]. All of these studies confirmed the overall picture of PBH formation, showing that the precise value of δ c depends on the initial perturbation profile.…”
Section: Introductionmentioning
confidence: 92%
See 3 more Smart Citations